Force of lifelong crystalline lens growth: chronic traumatic mechanical insult to the choroid. Issue 3 (March 2022) - Strenk, Lawrence M.; Guo, Suqin; Lu, Kenneth; Werner, Liliana; Strenk, Susan A.
Abstract : A previously unknown force produced by lifelong crystalline lens growth may represent a chronic mechanical traumatic insult to the uvea and be an IOP-independent modifiable risk factor for retinal disease. Abstract : Purpose: To calculate the forces applied to the uvea and retina as a result of lifelong crystalline lens growth. Design: Retrospective study. Setting: MRI Research, Inc., Middleburg Heights, Ohio; Institute of Ophthalmology and Visual Science UMDNJ–New Jersey Medical School, Newark, New Jersey; USC Psychology University of Southern California, Los Angeles. Methods: Magnetic resonance images were acquired from 15 phakic/pseudophakic eye pairs in patients with cataract (ages 46 to 83 years). Choroidal lengths were measured. The forces required to produce differences between phakic/pseudophakic choroidal lengths were calculated. Results: The length of the choroid is greater in the phakic eye compared with the corresponding pseudophakic eye (n = 15), and this difference increases with age ( P = .00006; power = 0.99). The corresponding choroidal strain also increases with age ( P = .00003, power = 0.99) as do the forces required to produce such a change in choroidal length ( P = .000008, power = 0.99). Conclusions: The authors theorize that lifelong crystalline lens growth applies a chronic, traumatic, mechanical insult to the uvea and retina. This previously unknown, ever-increasing, force appears to stretch the choroidal tissue and may be an intraocular pressure–independent modifiable risk factor for retinal disease. Implications exist for understanding the pathophysiology of retinal diseases in the aging eye that are often comorbid with cataracts, for example, glaucoma, macular degeneration, and diabetic retinopathy.